The Arabic Language Learning Planning Program at Tahfizul Qur’an Boarding School, Sungai Pinang - Febrina, Dina; M. Akil Fathur Rahman Syah; Wahyuni Saeran Abdullah (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the planning and implementation of Arabic language teaching at School Of Muhammadiyah Penyasawan Kampar Regency. The research employs a descriptive qualitative method, utilizing interviews and observations as data collection techniques. Primary data sources include the principal, vice principal for curriculum affairs, and Arabic language teachers, while secondary data consist of related literature. The findings indicate that lesson planning encompasses tools such as annual programs, semester programs, syllabi, and lesson plans (RPP), designed based on KMA 374. However, challenges such as limited teacher training and a lack of teaching materials hinder the implementation of the Independent Curriculum. The teaching process involves opening, core, and closing activities, with special attention given to student motivation and time allocation.